Sistem Informasi Pemilihan Peserta Program Indonesia Pintar (PIP) Dengan Metode K-Nearest Neighbor pada SD Negeri Pejuang V Kota Bekasi - Prihatin, Sandy Satyo; Atika, Prima Dina; Herlawati, Herlawati (Journal of Students‘ Research in Computer Science, 2021)
The selection of participants for the Smart Indonesia Program (PIP) is an activity to determine students who are eligible for assistance. This study aims to create an information system for the Selection of Participants for the Smart Indonesia Program (PIP) which will assist Administrative Staff and SD Negeri Pejuang V Bekasi City in determining eligible and ineligible participants for assistance. The method used in this information system uses the K-Nearest Neighbor algorithm. The K-Nearest Neighbor process is carried out by giving weight to the student data attributes and looking for the Euclidean distance, then sorted from the smallest distance, after sorting the student data then looking for the closest distance to the training data. The K-Nearest Neighbor algorithm in data training is very fast, simple, easy to learn, effective with large training data and is resistant to data containing incorrect or anomalous values. The results of this study obtained student data as many as 77 students, there are True Positive (TP) data of 5 data, False Positive (FN) of 7 data, True Negative (TN) of 65 data and False Negative (FP) of 0. Results The accuracy obtained is 90.90% with a value of k=10.